Studying The Effectiveness Of The Drug Meth Killer 90% S.P. Uzbekistan In The Fight Against The Cotton Bowl On The Cotton Plant (Texas Journal of Agriculture and Biological Sciences, 2026)
Meth Killer 90% s.p. It turned out to be an effective means in the fight against cotton bollworm at a rate of 0.3-0.4 kg/ha on cotton crops. At the specified consumption rate, the drug Met Killer 90% s.p. does not have a toxic effect on the growth and development of plants. Based on the results of the industrial field test, we believe that it is necessary to include the drug Met Killer 90% s.p. in the “List of ...” of the Republic of Uzbekistan. against cotton bollworm the norm is 0.3-0.4 kg/ha on cotton crops.